Antiobese function of platelet‐activating factor: increased adiposity in platelet‐activating factor receptor‐deficient mice with age. Issue 1 (7th October 2013) - Sugatani, Junko; Sadamitsu, Satoshi; Yamaguchi, Masahiko; Yamazaki, Yasuhiro; Higa, Ryoko; Hattori, Yoshiki; Uchida, Takahiro; Ikari, Akira; Sugiyama, Wataru; Watanabe, Tatsuo; Ishii, Satoshi; Miwa, Masao; et al.
Abstract : Platelet‐activating factor receptor (PAFR)‐deficient mice developed a more severe obese state characterized by higher body mass (~25%) and epididymal fat mass (~55%) with age than that of wild‐type (WT) littermates. PAFR‐deficient mice did not show changes in the expression of critical genes involved in anabolic and catabolic metabolism in adipose, liver, and muscle tissues between 6 and 36 wk. However, a 38–81% reduction in β3 /β1 ‐adrenergic receptor (AR) and uncoupling protein 1 (UCP1) mRNA and protein levels was observed in the interscapular brown adipose tissue (BAT) of PAFR‐deficient mice. Whereas a single injection of the β3 ‐adrenergic agonist, CL‐316, 243 (25 μg/kg) increased temperatures in the brown fat and rectums of WT mice, this increase in temperature was markedly suppressed in PAFR‐deficient mice. Acetyl‐CoA:lyso‐platelet‐activating factor (PAF) acetyltransferase, which is involved in PAF biosynthesis, and the PAF receptor were predominantly localized in BAT macrophages, whereas brown adipocytes possessed the enzyme and functional PAF receptors. The stimulation of brown adipocytes by PAF induced the expression of β3 ‐AR mRNA and protein (1.5‐ and 1.9‐fold, respectively), but not that of UCP1. These results indicate that obesity in PAFR‐deficient mice resulted from impaired BAT activity and suggest that the antiobese function of PAF occurs through β3 ‐AR/UCP1 expression in BAT.—Sugatani, J., Sadamitsu, S., Yamaguchi, M., Yamazaki, Y., Higa, R., Hattori, Y., Uchida, T., Ikari, A., Sugiyama, W., Watanabe, T., Ishii, S., Miwa, M., Shimizu, T. Antiobese function of platelet‐activating factor: increased adiposity in platelet‐activating factor receptor‐deficient mice with age. FASEB J . 28, 440–452 (2014). www.fasebj.org